1992
DOI: 10.1002/pen.760321002
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene composites. II: Structure‐property relationships in two‐ and three‐component polypropylene composites

Abstract: Two‐ and three‐component polypropylene (PP) blends and composites were prepared to study their structure/property relationships. Butadiene‐styrene (BDS) copolymers of low compatibility formed large particles of poor adhesion in PP resulting in inferior mechanical properties. Better miscibility of ethylene‐propylene‐diene (EPDM) elastomer results in more finely dispersed particles and the experimental results indicate a transition to an interpenetrating network (IPN)– like structure with increasing elastomer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Wilkinson et al 28 also found the same phenomenon in the PP/PA6/SEBS-g-MA ternary blends and attributed the shoulder peak to the secondary crystallization of PA6 component. [29][30][31] The extruded PA6 used in the study also exhibits this bimodal melting behavior under the same measurement condition. The conditions that reduce the mobility of chain segments after primary crystallization has occurred, such as rapid cooling 28 and crystallization at high degrees of undercooling, 2,28 can suppress the development of the low temperature shoulder and produce a melting endotherm with a single peak.…”
mentioning
confidence: 83%
“…Wilkinson et al 28 also found the same phenomenon in the PP/PA6/SEBS-g-MA ternary blends and attributed the shoulder peak to the secondary crystallization of PA6 component. [29][30][31] The extruded PA6 used in the study also exhibits this bimodal melting behavior under the same measurement condition. The conditions that reduce the mobility of chain segments after primary crystallization has occurred, such as rapid cooling 28 and crystallization at high degrees of undercooling, 2,28 can suppress the development of the low temperature shoulder and produce a melting endotherm with a single peak.…”
mentioning
confidence: 83%
“…Usually intermediate structures form in composites produced under practical conditions, a part of the filler is embedded into the elastomer phase, but individual elastomer droplets and filler particles can be also located in the matrix. Structure can be tailored by the control of interfacial adhesion through the use of appropriate coupling agents [23][24][25][26]. Functionalized polymers are used to control structure in polypropylene.…”
mentioning
confidence: 99%
“…Usually intermediate structures form in composites produced under practical conditions, a part of the filler is embedded into the elastomer phase, but individual elastomer droplets and filler particles can be also located in the matrix. Structure can be tailored by the control of interfacial adhesion through the use of appropriate coupling agents [18][19][20][21]. Functionalized polymers are used to control structure in polypropylene.…”
mentioning
confidence: 99%